Public policies and their ephemeral response in the cycle paths executed within the monumental area of Tacna, Perú 2023 - Vizcarra Silvestre, Ronny Fernando; Pajuelo Camones, Carlos Heraclides; Sotelo-Gonzáles, Soledad; Valdivia Oroya de Rodríguez, Nery Betty; Gonzáles Walstrohm , Carlos José (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
Public policies and the transient response to cycle paths implemented within the monumental area of Tacna, Peru, align with an international policy proposed by the Sustainable Development Goals related to SDG 11: Sustainable cities; where the national government is the main promoter of its execution in urban areas, this initiative aims to enhance the organization and accessibility of non-motorized vehicles, particularly during the pandemic and the post-pandemic period caused by Covid-19. The main objective is to determine the level of satisfaction of the collegiate architects of Tacna, relating it to the contribution of the cycle paths in the monumental area and interpret the ephemeral paradigm of efficient use, imposed on the city. The study employs a quantitative approach at a descriptive level, utilizing a survey based on a Likert scale. The survey evaluates conditions such as materials, basic security, institutional functioning, and the achieved results. The findings indicate low levels of acceptance across all four dimensions low.